2020
DOI: 10.3920/jiff2019.0034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of larval density, substrate moisture content and feedstock ratio on life history traits of black soldier fly larvae

Abstract: Performance and body composition of insect larvae depend on quality and quantity of their diet, and on biotic factors such as larval density. Experiments were undertaken to assess the effects of larval density, substrate moisture content and feedstock ratio on larval life history parameters of black soldier fly (BSF) in the laboratory. Four-day-old larvae were separately reared under six different densities (1, 2, 4, 6, 8 and 10 larvae/cm2) and at five substrate moisture content levels (40, 50, 60, 70 and 80%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…BSF colony was established in 2017 from larvae of wild-trapped Hermetia illucens populations breed since 2016 at the International Institute of Tropical Agriculture (IITA), Yaoundé, Cameroon. BSF egg clusters from the pre-established colony were incubated according to the method described by Dzepe et al [9]. After hatching, a total number of 48 000 four-day-old larvae were collected and divided into two equal groups used to test two feeding strategies (continuous and batch feeding strategies).…”
Section: Black Soldier Fly Colonymentioning
confidence: 99%
See 1 more Smart Citation
“…BSF colony was established in 2017 from larvae of wild-trapped Hermetia illucens populations breed since 2016 at the International Institute of Tropical Agriculture (IITA), Yaoundé, Cameroon. BSF egg clusters from the pre-established colony were incubated according to the method described by Dzepe et al [9]. After hatching, a total number of 48 000 four-day-old larvae were collected and divided into two equal groups used to test two feeding strategies (continuous and batch feeding strategies).…”
Section: Black Soldier Fly Colonymentioning
confidence: 99%
“…Therefore, there is a pressing need for developing multiple potential food waste valorization technologies to reduce as well as mitigate the adverse effects of food waste. Processing of organic waste using fly larvae is a relatively new concept which is currently attracting interest [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This could explain why the pupation period of the larvae group fed with banana peels was shorter than the group fed with coconut testa based on the likelihood of getting sugar and protein. On the other hand, the water content of the banana peels had a higher positive effect on the process of the accumulation of nutrients during the larval stage to be used in the pupation period (Cheng et al, 2017;Dzepe et al, 2019).…”
Section: The Pupation Period Developmentmentioning
confidence: 99%
“…A further key issue in terms of efficiency and quality is the water content. A recent study (Dzepe et al, 2020) in which five substrates moisture content levels (40, 50, 60, 70 and 80%) were tested, indicated that increasing the substrate moisture content reduces the larval feed reduction (mass reduction, %; Salomone et al, 2017), wet weight, development time, and body size and body thickness of the larvae. This is in line with another study (Lalander et al, 2020), which reported that adding too much water content reduced the biomass conversion ratio and survival rate of the larvae.…”
Section: Type Of Substratesmentioning
confidence: 99%